Does Information and Communication Technology Elevate Tax Revenue? Panel Data Analysis Using Indonesian Setting - Siswantoro (MUC Tax Research Institute, 2023)
Tax ratio in Indonesia is persistently below the international standard of 15%. Apart from that, there were only three periods recorded in the last 16 years where the realization of tax revenues exceeded the targets. This indicates that the tax authority’s performance in Indonesia is nonoptimal. It is necessary to integrate digitalization in the tax system by seeking the use of Information and Communication Technology (ICT) to maximize tax revenue performance. The aim of this research is to examine the impact of ICT developments with the dimensions of access and infrastructure, use and skills on tax revenues in 34 provinces in Indonesia in 2017-2021. This research also considers control variables including Gross Regional Domestic Product (GRDP), foreign direct investment, population, inflation and the Covid-19 pandemic. A total of 170 panel data were evaluated using a fixed effect model approach. All data was obtained from the Indonesian Statistics Bureau (BPS). The research results show that only the dimension of use has a positive and significant influence on regional tax revenues. The dimensions of access and infrastructure, and skills, have a positive but not significant influence on regional tax revenues. The control variables that influence tax revenues in Indonesia are GRDP, population, and the Covid-19 pandemic, while foreign investment and inflation have no significant effect on tax revenues. At the end, this research also suggests further studies to know the influence of dimensions of ICT use on tax revenues under various conditions.